Friction, Wear, and Scuffing Characteristics of Marine Engine Lubricants with Nanodiamond Particles. Issue 6 (1st November 2016) - Kim, Seung-Taek; Woo, Je-Yong; Lee, Young-Ze
ABSTRACT: Many kinds of additives are generally added to engine lubricants to improve performance. These chemical additives are harmful to both humans and the environment. For this reason, the research trend in the lubricant industry is to reduce the use of chemical additives in engine oils. Carbon materials like nanodiamonds are candidates among many physical additives. Nanodiamond particles are round, very hard, chemically stable, and highly heat conductible. In this research, nanodiamond particles were uniformly dispersed in marine engine lubricants. A matrix synthesis method was used for dispersion with various concentrations. Friction and wear tests were performed to measure the friction and wear amounts, and scuffing tests were performed. The friction coefficients were decreased with the addition of nanodiamond particles. Due to their octagonal and almost spherical shape, the particles could act as rolling contact elements between two lubricated sliding surfaces. In addition, it was found that there was a proper concentration of nanodiamond to minimize the wear amounts, which was 0.3 wt%. From the scanning electron microscopy (SEM) analysis many agglomerated particles were found on the sliding surfaces with a high concentration of particles over 0.3%. The excessive amount of nanodiamonds acted as abrasive debris and ploughed the contact surfaces. Finally, as the concentration of nanodiamonds increased, the scuffing life increased due to a reduction in friction, and the rate of temperature increase was reduced due to the high heat conductivity of nanodiamonds.